Toward a Software Model and a Specification Language for Next-Generation User Interfaces. - Shaer, Orit.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
As user interfaces evolve from traditional WIMP to 'reality based interfaces', developers are faced with a set of new challenges which are not addressed by current software tools and models. This paper discusses these challenges and presents a software model and specification language which are designed to simplify the development of non-WIMP interfaces such as virtual environments. Finally, we discuss our plans to extend this model to support physical interaction and dynamic adaptation of interfaces.